2016
DOI: 10.1186/s13046-016-0333-z
|View full text |Cite
|
Sign up to set email alerts
|

High expression of ID family and IGJ genes signature as predictor of low induction treatment response and worst survival in adult Hispanic patients with B-acute lymphoblastic leukemia

Abstract: BackgroundB-Acute lymphoblastic leukemia (B-ALL) represents a hematologic malignancy with poor clinical outcome and low survival rates in adult patients. Remission rates in Hispanic population are almost 30 % lower and Overall Survival (OS) nearly two years inferior than those reported in other ethnic groups. Only 61 % of Colombian adult patients with ALL achieve complete remission (CR), median overall survival is 11.3 months and event-free survival (EFS) is 7.34 months. Identification of prognostic factors is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 66 publications
(45 reference statements)
0
23
0
Order By: Relevance
“…ID family members are pivotal modulatory proteins that have been recognized to be downstream targets of a number of oncogenic pathways, making them attractive targets for the treatment of cancer ( 4 , 5 , 33 ). However, there are significant contradictions in the specific roles of different IDs in BC development ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ID family members are pivotal modulatory proteins that have been recognized to be downstream targets of a number of oncogenic pathways, making them attractive targets for the treatment of cancer ( 4 , 5 , 33 ). However, there are significant contradictions in the specific roles of different IDs in BC development ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitor of DNA binding/differentiation (ID) proteins, as a group of helix-loop-helix transcription factors, are individually fundamental to development and cell cycle control ( 1 ). Recently, loss- and gain-of-function studies have indicated the oncogenic effects of ID proteins in tumors, and have revealed associations between these proteins and malignant features, including transformative cellular phenotype, abnormal senility, facilitating proliferation and distant spreading ( 2 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The steady progress in the development of effective treatments has led to a cure rate of more than 80% in children with ALL, most of whom will lead healthy productive lives as long-term cancer survivors (1,2). Yet, studies are underway to ascertain the precise events that take place in the genesis of ALL, to enhance the clinical application of known risk factors and anti-leukemic agents, and to identify treatment regimens that may boost the generally low cure rates in adults and subgroups of children with high-risk leukemia (3)(4)(5). Approaches aimed at blocking associated miRNAs may serve as effective therapeutic strategies for treating ALL patients and may be valuable biomarkers for diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In developed societies, complete remission (CR) rates range between 85% and 90%; however, long-term overall survival (OS) rates remain between 40% and 50% [13][14][15][16], particularly as a result of relapse and disease progression. The MD Anderson Cancer Center (MDACC) group has reported CR rates above 90% and OS of 60% at 5 years in adolescent and young adult (AYA) ALL patients treated with hyper-CVAD and the Augmented Berlin-Frankfurt-Münster (ABFM) protocol [17].Unfortunately, the course of adult patients in Latin America yields less favorable results [18,19]. A study conducted in Brazil reported CR >90% and 5-year OS curves of 35% with the hyper-CVAD regimen [20].…”
mentioning
confidence: 99%